Implementation of Computer Based Systems for Effective Decisions in Acceptance of Vikar - Dharma Hardi, Shinta; Hutabarat, Hukendik; Rumahorbo, Benget; Willem, W.; Judica Pangaribuan, Mindo; Sudiby, Kusman; Paulus Saleky, Andre; Kristian Siburian, Henry; Jati Nugroho, Fibry; Kurniasih, Nuning; Mesran, M; Sianturi, Maringan; et al. (International Journal of Engineering and Technology, 2018)
The development of computer technology increasingly makes computers more popular in the community, so that it is easy to find computer usage in completing human work. The use of information technology is now increasingly developing with decision support-based information systems that can help decision makers in providing better decision decisions. Likewise in the process of receiving Vikar in the GKPI church. Vicar candidates must go through the selection stage and at the final stage a decision-based support system is used to provide the right decision, the prospective Vikar who can be accepted in the GKPI. In this study, ARAS method is used which is expected to solve problems related to multi-criteria-based decision processing.Â Â